Treatment Outcome for Head and Neck Squamous Cell Carcinoma in a Developing Country: University Malaya Medical Centre, Malaysia from 2003-2010 - Wong, Y.F.; Yusof, M.M.; Ishak, W.Z.W.; Alip, A.; Phua, V.C.E. (Asian Pacific Organization for Cancer Prevention, 2015)
Background: Head and neck cancer (HNC) is the eighth most common cancer as estimated from worldwide data. The incidence of HNC in Peninsular Malaysia was reported as 8.5 per 100,000 population. This study was aimed to determine the treatment outcomes for HNC patients treated in the Oncology Unit of University Malaya Medical Centre (UMMC). Materials and Methods: All newly diagnosed patients with squamous cell carcinoma of head and neck (HNSCC) referred for treatment to the Oncology Unit at UMMC from 2003-2010 were retrospectively analyzed. Treatment outcomes were 5-year overall survival (OS), cause specific survival (CSS), loco-regional control (LRC) and radiotherapy (RT) related side effects. Kaplan-Meier and log rank analyses were used to determine survival outcomes, stratified according to American Joint Committee on Cancer (AJCC) stage. Results: A total of 130 cases were analysed. Most cases (81.5%) were at late stage (AJCC III-IVB) at presentation. The 5-year OS for the whole study population was 34.4% with a median follow up of 24 months. The 5-year OS according to AJCC stage was 100%, 48.2%, 41.4% and 22.0% for stage I, II, III and IVA-B, respectively. The 5-year overall CSS and LCR were 45.4% and 55.4%, respectively. Late effects of RT were documented in 41.4% of patients. The most common late effect was xerostomia. Conclusions: The treatment outcome of HNSCC at our centre is lagging behind those of developed nations. Efforts to increase the number of patients presenting in earlier stages, increase in the use of combined modality treatment, especially concurrent chemoradiotherapy and implementation of intensity modulated radiotherapy, may lead to better outcomes for our HNC patients.